Year-round performance assessment of a ground source heat pump with multiple energy piles - Cui, Yuanlong; Zhu, Jie (Elsevier, 2018)
The year-round performance of a ground source heat pump (GSHP) with multiple energy piles (EPs) is investigated in this study based on a 3D transient heat transfer model. The GSHP heating and cooling capabilities are simulated and assessed according to thermal energy demands of an air conditioned domestic building, its coefficients of performance (COPs) obtained from numerical analyses and experimental tests are compared and the largest difference between them is less than 8%. The maximum heating and cooling COPs of the GSHP are 3.63 and 4.73 respectively in the first year operation period, and the soil final temperature is lower than its initial temperature, therefore the soil is not capable of recovering by itself due to the building unbalanced heating and cooling loads. Finally, the effects of the soil thermal properties on its temperature and the GSHP COPs are investigated and compared between the first year and tenth year operations, and it is found that the soil with low volumetric heat capacity and high thermal conductivity could achieve a quick temperature recovery.